The Lichenflora of Kryvyi Rig iron ore dumps (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
This article presents information about lichens of five Kryvyi Rig iron ore dumps. 58 species of lichens from 29 genera and 16 families were found. One species – and Trapelia obtegens (Th. Fr.) Hertel is rare for the champaign area of Ukraine. Most species of lichens are represented epiphytic (21) and saxicolous (20) ecological groups. Also noted 8 soil and 9 habitat generalists. Most often on iron ore dumps are species Candelariella aurella (Hoffm.) Zahlbr., Lecanora dispersa (Pers.) Röhl., Massjukiella polycarpa (Hoffm.) S.Y. Kondr., Fedorenko, S. Stenroos, Kärnefelt, Elix, J.S. Hur & A. Thell, Phaeophyscia orbicularis (Neck.) Moberg, Physcia adscendens (Fr.) H. Olivier, Rinodina pyrina (Ach.) Arnold and Xanthoria parietina (L.) Th. Fr.